Can School Children Support Ecological Research? Lessons from the Oak Bodyguard Citizen Science Project. (18th March 2020) - Castagneyrol, Bastien; Valdés-Correcher, Elena; Bourdin, Audrey; Barbaro, Luc; Bouriaud, Olivier; Branco, Manuela; Centenaro, Giada; Csóka, György; Duduman, Mihai-Leonard; Dulaurent, Anne-Maïmiti; Eötvös, Csaba B.; Faticov, Maria; et al.
Scientific knowledge in the field of ecology is increasingly enriched by data acquired by the general public participating in citizen science (CS) programs. Yet, doubts remain about the reliability of such data, in particular when acquired by schoolchildren. We built upon an ongoing CS program, Oak Bodyguards, to assess the ability of schoolchildren to accurately estimate the strength of biotic interactions in terrestrial ecosystems. We used standardized protocols to estimate attack rates on artificial caterpillars and insect herbivory on oak leaves. We compared estimates made by schoolchildren with estimates made by professional scientists who had been trained in predation and herbivory assessments (henceforth, trained scientists), and trained scientists' estimates with those made by professional scientists with or without expertise (untrained) in predation or herbivory assessment. Compared with trained scientists, both schoolchildren and untrained professional scientists overestimated attack rates, but assessments made by the latter were more consistent. Schoolchildren tended to overestimate insect herbivory, as did untrained professional scientists. Raw data acquired by schoolchildren participating in CS programs therefore require several quality checks by trained professional scientists before being used. However, such data are of no less value than data collected by untrained professional scientists. CS with schoolchildren can be a valuable tool for carrying out ecological research, provided that the data itself is acquired by professional scientists from material collected by citizens.